Superabsorbent hydrogel (SAH) as a soil amendment for drought management: A review - Saha, Abhisekh; Sekharan, Sreedeep; Manna, Uttam (Soil & tillage research, 2020)
[Display omitted] •Long-term drought affects the soil ecosystem and can initiate desertification.•SAH improves the soil-pore structure and water retention characteristics.•Plant growth and survival time increases with increasing SAH concentration.•Soil texture, salinity and application rate influence the performance of SAH.•SAH amendment can protect plant-soil ecosystem from drought stress. Drought is one of the worst natural disasters that affect the economic, social, and environmental status of any country. The long-term drought affects the soil ecosystem and can initiate desertification and deterioration of soil health. This leads to severe water distress, which is further aggravated by improper water management, poor irrigation practice, degradation of soil quality, and low water holding capacity of soil. Effective land management is the most feasible solution during drought. It is established that the utilization of superabsorbent hydrogel (SAH) as a soil amendment can improve soil structure, water-holding capacity, and plant available water content because of its hydrophilic three-dimensional network. However, there are contrasting observations in the existing literature related to the absorption capacity of SAH under different conditions, which may have an impact on drought management. This study purports to critically review the findings reported in the literature to reveal the influence of SAH addition for solving water stress conditions. The influence of SAH application on the physical properties of soil, such as water retention capacity, plant available water content, hydraulic conductivity, and infiltration, was investigated. This study brings out the discrepancies associated with the influence of SAH application in different textured soil, presence of salinity, and biodegradation of synthetic SAH. It was found that the application of SAH can reduce the evaporation loss and deep percolation, thereby increasing the plant growth and survival time in drought despite some reduction in swelling capacity under saline condition. The need for further studies for the development of biodegradable SAH and its performance evaluation under various environmental conditions has been summarized.